Legal Analysis of Law Enforcement In The Fraud Case At Bank Jago - Muhammad, Raihan; Makhfud, Amirul; Ananta, Bintang Rafli; Robbani, Muhammad Rizqi; Arsy, Fauzuld Nur (Journal Management & Economics Review (JUMPER), 2024)
This research analyzes a fraud case at Bank Jago involving the embezzlement of customer funds worth Rp1.3 billion by a former bank employee in 2023. This case is of concern because it reveals weaknesses in the internal monitoring system and the risk of abuse of authority. Using a normative legal approach and qualitative descriptive methods, this research examines the chronology of events, the perpetrator's modus operandi, and the effectiveness of applicable regulations. Research data was obtained from secondary sources such as official reports, statutory regulations, internal bank policies, and scientific articles. The research results show that weak internal supervision and unauthorized access are the main causes of fraud. The perpetrators used their authority to illegally unblock customer accounts and transfer funds to their personal accounts, which violates the ITE Law, Fund Transfer and TPPU. This research highlights the importance of applying advanced technology such as artificial intelligence and big data analytics to detect potential fraud, synergy between banking institutions and law enforcement officials, as well as employee training to build an antifraud culture. With these recommendations, it is hoped that research can contribute to improving the integrity and security of the banking sector in Indonesia.